2007
DOI: 10.1007/s12170-007-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure and cardiovascular disease

Abstract: Exposure to secondhand tobacco smoke (SHS) is associated with an increased risk of coronary heart disease (CHD) among nonsmokers, which has been estimated to be 20% to 30%. SHS may also increase the risk of stroke; however, the link is equivocal compared with that for CHD. In addition, data from clinical and animal studies support the biologic plausibility of the association between SHS exposure and CHD. Recent experimental evidence has provided further insights into the pathophysiology of the cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Unlike chronic active smoking where mechanisms of cumulative atherogenesis affect CVD risk, a synthesis of epidemiological and toxicological research suggests that SHS exposures may be an acute threat to the cardiovascular system with effects characterized by rapid onset [ 8 ]. In fact, many studies have indicated that short-term exposure to SHS may act as a trigger of acute clinical cardiovascular responses acting through multiple mechanisms including alteration of cardiovascular autonomic system and inflammation [ 9 - 12 ]. Changes in cardiovascular autonomic control are often assessed using measures of heart rate variability (HRV) which is the beat-to-beat variability of the R-R interval of successive normal beats on an electrocardiogram (ECG).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike chronic active smoking where mechanisms of cumulative atherogenesis affect CVD risk, a synthesis of epidemiological and toxicological research suggests that SHS exposures may be an acute threat to the cardiovascular system with effects characterized by rapid onset [ 8 ]. In fact, many studies have indicated that short-term exposure to SHS may act as a trigger of acute clinical cardiovascular responses acting through multiple mechanisms including alteration of cardiovascular autonomic system and inflammation [ 9 - 12 ]. Changes in cardiovascular autonomic control are often assessed using measures of heart rate variability (HRV) which is the beat-to-beat variability of the R-R interval of successive normal beats on an electrocardiogram (ECG).…”
Section: Introductionmentioning
confidence: 99%
“…Eichner et al (2010) [ 5 ] reported an elevated risk of nonfatal CVD for current smokers compared to non-smokers among American Indians. Current epidemiologic evidence indicates that exposure to ETS may increase risk of cardiovascular disease by 25–30%, although recent studies suggest this risk may be larger [ 9 , 10 ]. The effects of ETS on CVD are, on average, 80% to 90% as large as those from active smoking [ 11 ].…”
Section: Introductionmentioning
confidence: 99%